Negative electrode for all-solid-state battery and all-solid-state battery comprising same

By using a combined structure of crystalline carbon layer and amorphous carbon layer in the negative electrode of an all-solid state battery, a carbon defect structure and nanopores are formed, and solid electrolyte materials are embedded, the contact characteristics and life problems between the negative electrode and the solid electrolyte are solved, and the contact characteristics and life of the negative electrode are achieved. High energy density and stability.

CN119252860APending Publication Date: 2025-01-03LG ENERGY SOLUTION LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411561095.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2020-11-10
Filing Date
2021-10-14
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The contact characteristics and life characteristics of existing all-solid state batteries between the negative electrode and the solid electrolyte are insufficient, resulting in low energy density and stability, and the formation of lithium dendrites affects battery life.

Method used

Using the negative electrode composed of crystalline carbon layer and amorphous carbon layer, the amorphous carbon layer forms carbon defect structure and nanopores through plasma oxidation treatment, and embedded solid electrolyte materials to ensure that lithium ions are fully inserted and uniformly electrodeposited, and avoid lithium dendrites. Grow.

Benefits of technology

Excellent contact characteristics, low interface resistance and high ionic conductivity between the negative electrode and the solid electrolyte are achieved, which significantly improves the energy density and life characteristics of the battery and inhibits the formation of lithium dendrites.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119252860A_ABST
    Figure CN119252860A_ABST
Patent Text Reader

Abstract

The present invention relates to a negative electrode for an all-solid-state battery capable of providing an all-solid-state battery exhibiting excellent contact characteristics and improved lifespan characteristics between a negative electrode and a solid electrolyte, and an all-solid-state battery comprising the same.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of PCT international application PCT / KR2021 / 014241, with an application date of October 14, 2021. The original application is an invention patent application. The application number entering the Chinese national phase is 202180008524.3, and the name is "Negative electrode for all-solid-state batteries and all-solid-state batteries including the negative electrode". Technical Field

[0002] CROSS-REFERENCE TO RELATED APPLICATIONS

[0003] This application claims the benefit of Korean Patent Application No. 10-2020-0149184 filed in the Korean Intellectual Property Office on November 10, 2020, the disclosure of which is incorporated herein by reference in its entirety.

[0004] The present disclosure relates to an anode for an all-solid-state battery and an all-solid-state battery including the anode, which can provide an all-solid-state battery exhibiting excellent contact characteristics between the anode and a solid electrolyte and improved life characteristics. Background Art

[0005] Secondary batteries are mainly used in small fields such as mobile devices and laptops, but recently their application direction has been expanded to medium and large fields, and mainly to fields related to energy storage systems (ESS) or electric vehicles (EV) that require high energy and high output. For such medium and large secondary batteries, unlike small secondary batteries, not only are the operating environments such as temperature and shock harsh, but more batteries must be used. Therefore, it is necessary to have excellent performance or a suitable price while ensuring safety. Since most commercialized secondary batteries currently use liquid electrolytes in which lithium salts are dissolved in organic solvents, they have potential risks of fire and explosion, including leakage.

[0006] Therefore, the development of all-solid-state batteries has been carried out recently. All-solid-state batteries are batteries that use solid electrolytes instead of liquid electrolytes, and have the advantage of higher thermal stability than existing lithium secondary batteries using liquid electrolytes. In addition, since all-solid-state batteries are superior to existing lithium secondary batteries in terms of high energy density and output characteristics, simplification of manufacturing processes, and large-scale / compactness of batteries, people have recently focused on the research and interest in all-solid-state batteries.

[0007] On the other hand, in the case of existing all-solid-state batteries, as with existing lithium secondary batteries, graphite anodes are mainly used. However, in recent years, in order to further improve the capacity characteristics of batteries, the use of lithium metal anodes or anodes using silicon-based active materials has been widely discussed and studied. Since both these lithium metal anodes and silicon-based anodes have high theoretical capacities, high capacity and energy density can be achieved.

[0008] However, when a lithium metal negative electrode is used, during the initial charge / discharge process of the battery, the lithium moving from the positive electrode to the negative electrode is laminated on the surface of the negative electrode in the form of dendrites to form lithium dendrites, which has the disadvantage of deteriorating the life characteristics and stability of the battery. In addition, the silicon-based negative electrode also has the disadvantage of causing a large volume change during the charge / discharge process, thereby deteriorating the life characteristics of the battery. Therefore, there is a continuous need to develop a negative electrode and / or an all-solid-state battery that has improved life characteristics, etc. while achieving higher capacity and energy density.

[0009] In addition, since all-solid-state batteries contain solid electrolytes, in order to fully exert the performance of such all-solid-state batteries, it is necessary to ensure sufficient contact characteristics between each electrode and the solid electrolyte and achieve high ion conductivity. However, due to the characteristics of the solid electrolyte, it is difficult to penetrate into each electrode, and it is not easy to ensure sufficient contact area. All-solid-state batteries that ensure sufficient contact characteristics between the electrodes and the solid electrolyte, low interface resistance, and high ion conductivity have not yet been properly developed.

[0010] Due to the above-mentioned problems of the prior art, there is a continuous demand for the development of all-solid-state battery-related technologies that exhibit excellent contact characteristics between electrodes and solid electrolytes and improved life characteristics. Summary of the invention

[0011] Technical issues

[0012] The present disclosure provides an anode for an all-solid-state battery capable of providing an all-solid-state battery that exhibits excellent contact characteristics between the anode and a solid electrolyte and improved life characteristics while exhibiting high energy density.

[0013] Furthermore, the present disclosure provides an all-solid-state battery including the anode, the all-solid-state battery exhibiting high energy density, improved lifespan characteristics, excellent contact characteristics between the anode and a solid electrolyte, and low interface resistance.

[0014] Technical Solution

[0015] According to one aspect of the present disclosure, there is provided a negative electrode for an all-solid-state battery, comprising:

[0016] Crystalline carbon layer;

[0017] an amorphous carbon layer including a carbon defect structure formed on the crystalline carbon layer and formed of electron-deficient carbon atoms, and wherein nano-scale pores are formed in the carbon defect structure; and

[0018] A solid electrolyte material is formed in the pores of the amorphous carbon layer.

[0019] According to another aspect of the present disclosure, there is provided an all-solid-state battery, comprising:

[0020] a positive electrode, the positive electrode comprising a positive electrode current collector and a lithium composite oxide-based positive electrode active material layer formed on the positive electrode current collector;

[0021] the negative electrode as described above; and

[0022] An additional solid electrolyte layer is interposed between the positive electrode and the negative electrode.

[0023] Beneficial Effects

[0024] The negative electrode of the present disclosure not only does not include or minimally includes a separate active material layer formed three-dimensionally, such as a separate lithium metal film, but also includes an amorphous carbon layer containing a carbon defect structure and a plurality of nanopores formed by electron-deficient carbon atoms by chemically treating a crystalline carbon layer.

[0025] By forming an amorphous carbon layer containing such a carbon defect structure, an active material layer such as a lithium metal film formed in the form of a three-dimensional additional film in a battery or the like using an existing lithium metal negative electrode can be eliminated or reduced. Therefore, the growth of lithium dendrites from such a lithium metal film or the like can be fundamentally suppressed.

[0026] In addition, in the amorphous carbon layer, since a large number of electron-deficient carbon atoms are included in the carbon defect structure, a large number of lithium ions and / or lithium compounds containing lithium ions can be inserted while providing electrons to these carbon atoms. In addition, by using such lithium ions as nuclei, lithium metal can be uniformly electrodeposited around them. Therefore, such an amorphous carbon layer can induce uniform lithium electrodeposition formed in two dimensions on the same plane, and the lithium metal thus electrodeposited can serve as an active material layer with a lithium ion source. Therefore, the negative electrode of the present disclosure can achieve a high energy density comparable to that of the case where an existing lithium metal negative electrode is applied.

[0027] In addition, since the solid electrolyte material can be filled in a large number of nanopores formed in the amorphous carbon layer, it is possible to ensure sufficient contact area between the negative electrode, the lithium metal as the active material layer, and the solid electrolyte filled in the nanopores. Therefore, it is possible to achieve excellent contact characteristics, low interface resistance, and high ionic conductivity between the negative electrode and the solid electrolyte.

[0028] As a result, when the negative electrode of the present disclosure is used, an all-solid-state battery can be provided that suppresses the formation of lithium dendrites, has a high energy density comparable to that of a lithium metal negative electrode, exhibits improved life characteristics, and ensures sufficient contact characteristics between the negative electrode and the solid electrolyte.

[0029] Such an all-solid-state battery can exhibit excellent battery performance and life characteristics, and can be very preferably used as a next-generation battery applied to electric vehicles and the like. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1a and Figure 1b The SEM and TEM analysis results of the surface of each carbon layer in the steps before forming the solid electrolyte material during the manufacturing process of the negative electrode of Comparative Example 1 and Example 1 are shown;

[0031] Figure 2a to Figure 2c is a diagram showing the analysis results for each production step of Example 1 after elemental analysis of carbon paper and a negative electrode by EDS and corresponding SEM images;

[0032] Figure 3 is a diagram showing the XPS analysis results of each carbon layer in the step before forming the solid electrolyte material in the manufacturing process of the negative electrode of Comparative Example 1 and Example 1;

[0033] Figure 4 is a diagram showing the results of Raman spectroscopy analysis of each carbon layer in a step before forming a solid electrolyte material in the manufacturing process of the negative electrode of Comparative Example 1 and Example 1;

[0034] Figure 5 is a diagram showing the BET analysis results of each carbon layer in the step before forming the solid electrolyte material in the manufacturing process of the negative electrode of Comparative Example 1 and Example 1;

[0035] Figures 6a to 6d respectively show the results of SEM analysis of the negative electrode surfaces (front surface and rear surface) after forming the solid electrolyte materials in Example 1 and Comparative Example 1; and

[0036] Figure 7 3 is a graph showing comparative evaluation results of the life characteristics of the batteries of Comparative Example 2, Comparative Example 3, and Example 2. DETAILED DESCRIPTION

[0037] Throughout the specification, when a part is said to "comprise" a certain component, it means that the component may further include other components without excluding other components unless otherwise specified. The term "approximately or approximately" or "substantially" is intended to have a meaning close to a numerical value or range specified with an allowable error, and is intended to prevent the accurate or absolute numerical value disclosed for the purpose of understanding the present disclosure from being illegally or unfairly used by any unreasonable third party. The term "step of doing something" or "step of something" used throughout the specification does not mean a step for something.

[0038] Throughout the specification, the term "combination thereof" included in the Markush type description refers to a mixture or combination of one or more selected from the group consisting of components of the Markush type description, thereby meaning that the present disclosure includes one or more selected from the Markush group.

[0039] Based on the above definitions, embodiments of the present disclosure will be described in detail. However, these embodiments are presented for illustrative purposes only, and the present disclosure is not limited thereto, and the present disclosure is only limited by the claims described below.

[0040] Anode for all-solid-state batteries

[0041] According to one embodiment of the present disclosure, there is provided a negative electrode for an all-solid-state battery, comprising:

[0042] Crystalline carbon layer;

[0043] an amorphous carbon layer including a carbon defect structure formed on the crystalline carbon layer and formed of electron-deficient carbon atoms, and wherein nano-scale pores are formed in the carbon defect structure; and

[0044] A solid electrolyte material is formed in the pores of the amorphous carbon layer.

[0045] The negative electrode of one embodiment is manufactured by plasma oxidation treatment of the surface of a crystalline carbon fabric providing a crystalline carbon layer, surface coating and carbonization of a metal organic framework (MOF) to form an amorphous carbon layer, and applying a slurry coating method, etc. on the amorphous carbon layer in the same manner as the manufacturing method described later to form a solid electrolyte material.

[0046] As a result of such chemical treatment of the crystalline carbon layer, a large number of electron deficient carbon atoms are formed on the crystalline carbon layer, and an amorphous carbon layer having a network structure including a carbon defect structure containing these electron deficient carbon atoms is also formed.

[0047] Furthermore, in the amorphous carbon layer, while the metal organic framework is carbonized and decomposed, a large number of nanopores (vacancies) having a size of 0.5 nm to 2 nm, or 0.8 nm to 1.5 nm, or 1.0 nm to 1.2 nm may be formed in the carbon defect structure.

[0048] For reference, the amorphous characteristics of the amorphous carbon layer, the formation of a carbon defect structure (formation of electron-deficient carbon atoms), and the formation of a large number of nanopores can be confirmed by TEM analysis, XPS analysis, Raman spectroscopy analysis, and BET analysis described later.

[0049] The amorphous carbon layer includes a large number of electron-deficient carbon atoms, and a large number of nanopores with a size of 0.5 nm to 2 nm, more specifically 1.0 nm to 1.2 nm, are formed. Therefore, electrons are provided from the conduction band of lithium used to provide electrons to carbon atoms to the valence band of the carbon defect structure, so that lithium and / or lithium-containing compounds (e.g., lithium carbide compounds in the form of Li3C8) with a large amount of lithium ions can be well adsorbed, bonded and intercalated into electron-deficient carbon atoms. In addition, the lithium ions embedded in this way act as a kind of nucleus, and lithium metal can be uniformly electrodeposited around the carbon defect structure centered on the lithium ions.

[0050] In one example, lithium ions, etc. and lithium metal electrodeposited around them can be embedded and two-dimensionally form a large number of nanopores, and can be used as a lithium ion source for the negative electrode. Therefore, in the negative electrode of one embodiment, the lithium ion source can be two-dimensionally included on the same plane as (or inside) the amorphous carbon layer. Therefore, this amorphous carbon layer itself can be used as an active material layer having a lithium ion source (lithium metal electrodeposited on the amorphous carbon layer) contained in a two-dimensional plane, so that even if a lithium metal film or the like formed in the form of a three-dimensional additional film is not substantially added, a high energy density comparable to that of the case where an existing lithium metal anode is applied can be achieved.

[0051] In addition, since the lithium ion source can be two-dimensionally formed in the carbon defect structure of the amorphous carbon layer without substantially adding a lithium metal film in the form of a three-dimensional additional film, the growth of lithium dendrites and the like from a separate lithium metal film or the like further formed on the negative electrode can be fundamentally suppressed. Therefore, an all-solid-state battery including a negative electrode of one embodiment can exhibit significantly improved life characteristics and safety.

[0052] In addition, since the solid electrolyte material can be filled in a large number of nanopores formed in the amorphous carbon layer, it is possible to ensure sufficient contact area between the negative electrode, the electrodeposited lithium metal as the active material layer, and the solid electrolyte filled in the nanopores. Therefore, it is possible to achieve excellent contact characteristics, low interface resistance, and high ionic conductivity between the negative electrode and the solid electrolyte.

[0053] Therefore, when using a negative electrode of one embodiment, an all-solid-state battery can be provided, which suppresses the formation of lithium dendrites, exhibits improved life characteristics, etc., and also has a high energy density comparable to the case of applying a lithium metal negative electrode, and ensures sufficient contact characteristics between the negative electrode and the solid electrolyte.

[0054] On the other hand, various properties of the amorphous carbon layer, such as non-crystallinity, formation of carbon defect structure (formation of electron-deficient carbon atoms), and formation of multiple nanopores, can be confirmed by performing TEM analysis, XPS analysis, Raman spectroscopy analysis and BET analysis on the negative electrode surface (e.g., amorphous carbon layer).

[0055] First, the results of TEM analysis can confirm that the amorphous carbon layer is formed by disordered amorphous carbon atoms. In addition, through the TEM image, it can be confirmed that it is formed in the form of multiple graphene layers similar to having a thickness of about 1nm to 100nm, or about 2nm to 70nm, and it is formed in the form of multiple defective layers.

[0056] In addition, when the amorphous carbon layer is subjected to XPS analysis, it can be confirmed that a large number of nanopores (vacancies) are formed due to the carbonization and decomposition process after the metal organic framework is formed during the manufacturing process. In addition, according to the results of XPS analysis, it can be confirmed that the carbon defect structure containing electron-deficient carbon atoms, such as a separate peak derived from nanopores. Specifically, the intensity ratio of the peak derived from the separate peak of this carbon defect structure / derived from the carbon with sp2 orbital hybridization structure (normal carbon without electron-deficient state) is 0.3 or greater, or 0.35 to 0.50, or 0.4 to 0.45, which confirms that the electron-deficient carbon atoms and the carbon defect structure including the electron-deficient carbon atoms are formed in a considerable proportion and high density.

[0057] Furthermore, the Raman spectroscopy analysis of the amorphous carbon layer confirmed that the carbon defect structure originated from the 1500 cm -1 Below, or 1100-1500cm -1 The peak (D band; peak of electron-deficient carbon originating from carbon defect structure) shows a peak equal to or greater than 1500 cm -1 and 2000cm -1The intensity of the peak observed below (G band; peak derived from normal carbon having a graphitic structure). More specifically, the intensity ratio defined as the peak of the D band / the peak of the P band may be 1 or more, or 1 to 1.5, or 1.1 to 1.3.

[0058] Even through the results of Raman spectroscopy analysis, it can be confirmed that electron-deficient carbon atoms and carbon defect structures including the electron-deficient carbon atoms are formed at a considerable ratio and high density on the amorphous carbon layer included in the negative electrode of one embodiment.

[0059] In addition, according to the results of Raman spectroscopy analysis of the amorphous carbon layer, at 2500 cm -1 Above, or 2500-2900cm -1 , or 2600-2800cm -1 In the region of , an additional broad peak can be confirmed. Thus, it can be confirmed that the amorphous carbon layer may have a shape including a plurality of carbon layers.

[0060] Furthermore, even by BET surface analysis using nitrogen adsorption, the formation of a large number of nanopores included in the amorphous carbon layer can be confirmed, and the specific analysis results thereof are also described in the experimental examples described later.

[0061] As described above, in the amorphous carbon layer, since a carbon defect structure including a plurality of nanopores and electron-deficient carbon atoms is formed at a high density, lithium ions and / or lithium compounds can be two-dimensionally intercalated through the carbon defect structure and the nanopores, and lithium metal electrodeposited around these lithium ions or the like can be two-dimensionally included on the amorphous carbon layer. Lithium ions and the like and lithium metal can be used as a lithium ion source for the negative electrode.

[0062] Therefore, although a lithium metal film or the like additionally formed on the negative electrode in the form of a three-dimensional separation film is not substantially applied, the amorphous carbon layer includes a high-density lithium ion source formed two-dimensionally therein, and it can be used as an active material layer by itself. Therefore, an all-solid-state battery including a negative electrode of one embodiment can exhibit high capacity and high energy characteristics comparable to or higher than existing lithium metal batteries. In addition, problems such as three-dimensional growth of lithium dendrites outside the electrode from a lithium metal film or the like formed in the form of a separate film can also be fundamentally suppressed, thereby an all-solid-state battery including a negative electrode of one embodiment can exhibit significantly improved life characteristics and safety.

[0063] On the other hand, in the negative electrode of the above-described embodiment, the solid electrolyte material is contained in the nanopores of the amorphous carbon layer. Since such a solid electrolyte material is contained in a plurality of nanopores on the negative electrode, the solid electrolyte can have a large contact area with the negative electrode. In addition, lithium metal serves as an active material layer or the like. Therefore, the all-solid-state battery including the negative electrode of one embodiment can exhibit sufficient contact characteristics between the negative electrode and the solid electrolyte, low interfacial resistance, and high ionic conductivity.

[0064] Such a solid electrolyte material can be formed, for example, by coating and drying a slurry composition including a solid electrolyte, a binder, and a solvent on the amorphous carbon layer. Therefore, the solid electrolyte material can be impregnated and formed in the nanopores. In addition, in the negative electrode finally formed by this method, the solid electrolyte material present in the nanopores may include a solid electrolyte and a binder.

[0065] The type of the solid electrolyte is not particularly limited, and any solid electrolyte known to be usable in an all-solid-state battery before, such as an oxide-based, sulfide-based, or polymer-based solid electrolyte, can be used without particular limitation. However, considering the slurry coatability and high ionic conductivity of the solid electrolyte material and the sulfide-based solid electrolyte, a sulfide-based solid electrolyte can be appropriately used.

[0066] Such a sulfide-based solid electrolyte can include, for example, a sulfide-based compound represented by the following Chemical Formula 1. Among various sulfide-based compounds, an argyrodite-based compound showing high ionic conductivity and excellent coatability, such as a complex of Li2S-P2S5, can be preferably used:

[0067] [Chemical Formula 1]

[0068] M 1 a M 2 b S c X 1 d

[0069] In Chemical Formula 1, M 1 is at least one selected from alkali metals and alkaline earth metals, M 2 is Sb, Sn, Mg, Ba, B, Al, Ga, In, Si, Ge, Pb, N, P, As, Bi, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Y, Zr, Nb, Mo, Tc, Ru, Rh, Pd, Ag, Hf, Ta, W, or La, and X 1 is F, Cl, Br, I, Se, Te, or O, 0 < a ≤ 6, 0 < b ≤ 6, 0 < c ≤ 6, and 0 ≤ d ≤ 6.

[0070] In addition, the binder included in the solid electrolyte is a component added in consideration of slurry coating processability and adhesion of the solid electrolyte to the negative electrode, and any polymer binder previously known to be useful for forming an electrode such as a positive electrode or a negative electrode may be used without particular limitation.

[0071] Examples of such a polymer adhesive may include a butadiene rubber adhesive such as an acrylic adhesive, a polyvinylidene fluoride (PVDF)-based adhesive, a polytetrafluoroethylene (PTFE)-based adhesive, or a butadiene rubber-based adhesive, and needless to say, various polymer adhesives may be used in addition to these.

[0072] On the other hand, in the negative electrode of one embodiment described above, since the crystalline carbon layer supporting the amorphous carbon layer is formed of a crystalline carbon fabric or the like, it includes a plurality of carbon fibers and may have a thickness of 1 μm to 50 μm, or 2 μm to 30 μm, or 1 μm to 10 μm. Therefore, the negative electrode may exhibit appropriate mechanical and electrochemical characteristics.

[0073] The crystalline carbon layer may serve as a negative electrode current collector while supporting the amorphous carbon layer serving as an active material layer, whereby in the negative electrode of one embodiment, a separate metal current collector may also be omitted.

[0074] However, the negative electrode of one embodiment may include only a crystalline carbon layer used as a current collector, an amorphous carbon layer used as an active material layer containing the above-mentioned lithium ion source, and a solid electrolyte material formed in the nanopores of the amorphous carbon layer, but in addition, the negative electrode may further include a metal current collector for supporting the crystalline carbon layer, such as a copper current collector, a nickel current collector, or a stainless steel (SUS) current collector. Since this additional metal current collector can follow the configuration of the metal current collector in the electrode of a general all-solid-state battery or a lithium secondary battery, additional description thereof will be omitted.

[0075] Negative electrode manufacturing method

[0076] On the other hand, the negative electrode for an all-solid-state battery as described above can be manufactured by a method comprising the following steps: subjecting a crystalline carbon fabric comprising a plurality of carbon fibers to an oxygen plasma treatment to oxidize the surface; reacting the surface-oxidized crystalline carbon fabric, a nitrogen precursor, and a metal precursor to form a carbon fabric coated with a metal organic framework (MOF); calcining and carbonizing the carbon fabric coated with the metal organic framework at a temperature of 700° C. or higher to form an amorphous carbon layer on the crystalline carbon fabric; and coating a slurry composition containing a solid electrolyte, a binder, and a solvent on the amorphous carbon layer and drying it.

[0077] In addition, after forming the negative electrode in this manner, the method may further include causing the negative electrode or a battery including the negative electrode to undergo an electrochemical reaction to bind lithium ions or a lithium carbide compound to the amorphous carbon layer and electrodeposit lithium metal around the lithium ions or the lithium carbide compound.

[0078] According to such a manufacturing method, the crystalline carbon fabric corresponding to the crystalline carbon layer can be subjected to oxygen plasma treatment to oxidize the surface, and the surface-oxidized crystalline carbon fabric can be reacted with a nitrogen precursor and a metal precursor to form a carbon fabric having a metal organic framework (MOF). Then, as it is subjected to high-temperature calcination and carbonization to decompose and remove the metal organic framework, a carbon defect structure formed by electron-deficient carbon atoms and an amorphous carbon layer including the carbon defect structure can be formed in the portion where the metal organic framework is formed.

[0079] Subsequently, a solid electrolyte, for example, a slurry composition including a sulfide solid electrolyte, a binder, and a solvent is coated on the amorphous carbon layer and dried so that a solid electrolyte material including the solid electrolyte and the binder can be impregnated and formed in the nanopores of the amorphous carbon layer.

[0080] In addition, optionally, the solid electrolyte material electrochemically reacts with the negative electrode formed in the nanopore or a battery including the negative electrode, lithium ions or lithium carbide compounds are embedded in the amorphous carbon layer, and lithium metal is electrodeposited around it. Thus, a two-dimensionally formed lithium ion source can be formed in the amorphous carbon layer, which makes it possible to manufacture a negative electrode of one embodiment showing the above-mentioned excellent characteristics.

[0081] As described above, lithium ions or lithium metal can be two-dimensionally embedded and formed around the carbon defect structure in the amorphous carbon layer. Therefore, unlike a lithium metal thin film added three-dimensionally alone, lithium dendrite growth and the like are not caused thereby. In addition, lithium metal and the like are used as a lithium ion source for the negative electrode, so that the amorphous carbon layer including the lithium metal and the like itself can be used as an active material layer.

[0082] In the manufacturing method of other embodiments, as the crystalline carbon fabric, for example, carbon paper formed of carbon fibers having a diameter of 1-8 μm or 3-5 μm may be used, and any other equivalent crystalline carbon fabric may be used without particular limitation.

[0083] Furthermore, in the oxygen plasma treatment step, one surface or both surfaces of the crystalline carbon fabric may be surface-treated with oxygen plasma or a mixed gas plasma in which an inert gas such as oxygen and argon is mixed, thereby performing surface oxidation, which makes it possible to define a portion where a metal organic framework and a carbon defect structure are later formed.

[0084] In addition, in the step of forming the carbon fabric coated with the metal organic framework, the type of the metal organic framework or the type of the nitrogen precursor and the metal precursor used to form the metal organic framework is not particularly limited. This is because, in the manufacturing method of another embodiment, the metal organic framework is carbonized in a subsequent step to remove all remaining metal and organic components except carbon, and the carbon component also only contributes to the formation of the carbon defect structure.

[0085] However, specific examples of the metal organic framework that can be formed in the above step may include at least one compound selected from the group consisting of: Zn2DOT(MOF-74), Cu2(BDC-Br)2(H2O)2(MOF-101), Zn4O(BTB)2(MOF-177), [Fe3O(BDC)3(DMF)3][FeCl4].(DMF)3(MOF-235), Al(OH)(BPYDC)(MOF-253), Zn4O(BDC)3.7DEF.3H2O(IRMOF-1(MOF-5)), Zn4O(TPD C)3.17DEF.2H2O(IRMOF-16), Zr6O6(BDC)6(UiO-66), Zr6O6(BPDC)6(UiO-67), Zr6O6(TPDC)6(UiO-68), Al(OH)(BDC)(MIL-53), Al(O H)(BDC-NH2)(MIL-53(Al)-NH2), Fe3O(MeOH)3(O2CCH=CHCO2)3.MeCO2.nH2O(MIL-88A), Fe3O(MeOH)3(O2C(CH2)2CO2)3.AcO.(MeOH) 4.5 (MIL-88-Fe), 2Fe3O(OH)(H2O)2(BDC-Me2)3(MIL-88B-4CH3), Fe III 3O(H2O)2F.(BTC)2.nH2O(MIL-100-Fe), Cr3O(H2O)2F.(BDC)3.nH2O(MIL-101), Cu3(BTC)2(HKUST-1(MOF-199)), Gd2(BDC-NH2)3(DMF)4(LIC -10), Zn(MIM)2(ZIF-8), Zn(FIM)2(ZIF-90), Cu2(PZDC)2(4,4'-BPY)(CPL-2), [Cu(HFBBA)(phen)2](H2HFBBA)2(H2O)(HCO2)(F-MOF-1), and Cu 24 (m-BDC) 24 (DMF) 14 (H2O)10 (MOP-1) In addition to these, all various metal organic frameworks that can be formed on a carbon layer can be formed without particular limitation.

[0086] However, in order to appropriately form a carbon defect structure through the formation and carbonization of such a metal organic framework, a metal organic framework in the form of a metal zeolite-imidazole structure such as ZIF-8 may be preferably formed.

[0087] In addition, those skilled in the art can appropriately select and use nitrogen precursors and metal precursors corresponding thereto according to the type of metal organic framework. For example, when a metal organic framework is formed in the form of a metal zeolite-imidazole structure, an imidazole-based compound (such as methylimidazole) can be preferably used as a nitrogen precursor. In addition, various nitrogen precursors can also be selected and used according to the type of the above-mentioned metal organic framework.

[0088] In addition, as to the type of the metal precursor reacting with the nitrogen precursor, it is obvious to those skilled in the art that they can select and use a suitable metal-containing compound according to the type of the metal organic framework described above.

[0089] Examples of the metal precursor include at least one metal-containing compound selected from the group consisting of zinc (Zn), aluminum (Al), copper (Cu), zirconium (Zr), iron (Fe), chromium (Cr), and gadolinium (Gd), and various salts such as nitrates, hydroxides or sulfates of these metals, or compounds in the form of hydrates and / or solvates thereof, without particular limitation.

[0090] On the other hand, in the step of forming the carbon fabric coated with the above-mentioned metal organic framework, the surface-oxidized crystalline carbon fabric, the nitrogen precursor and the metal precursor can be reacted in a polar organic solvent (such as water or methanol) under stirring, and after the reaction, washing and drying steps can be further performed using a polar organic solvent. The specific conditions for performing these washing and drying steps are specifically described in the embodiments described later.

[0091] On the other hand, after the carbon fiber fabric coated with the metal organic framework is formed, calcination and carbonization may be performed at a temperature of 700° C. or higher, or 700° C. to 1300° C., or 800° C. to 1200° C. When such a carbonization step is performed, the metal organic framework is carbonized, decomposed, and removed, and an amorphous carbon layer including the above-mentioned carbon defect structure may be formed.

[0092] Subsequently, optionally, an inorganic impurity removal step using hydrochloric acid, a washing step, and a drying step may be further performed.

[0093] Then, a step of coating a slurry composition containing a solid electrolyte, a binder and a solvent on the amorphous carbon layer and selectively drying it may be performed. At this time, in order to uniformly form a solid electrolyte material containing a solid electrolyte and a binder in the nanopores, the coating step may be performed by a rod coating or dip coating method.

[0094] However, since specific types of the solvent contained in the slurry composition and specific performance conditions of the coating step are well known through known Korean Patent No. 1506833 and the like, additional description thereof will be omitted.

[0095] On the other hand, after forming the solid electrolyte material by the above method, the negative electrode is electrochemically reacted, and lithium ions or lithium carbide compounds are combined and embedded in the amorphous carbon layer, and by using lithium ions or the like as nuclei, lithium metal can be electrodeposited around them.

[0096] This electrochemical reaction may be performed as a separate lithium ion insertion reaction or lithium metal electrodeposition reaction during the manufacture of the negative electrode, but this reaction may be replaced by the performance of the initial charge / discharge step after the manufacture of the lithium secondary battery. For example, lithium ions or lithium carbide compounds are combined by an electrochemical reaction that occurs naturally during the initial charge / discharge step, and the insertion of lithium ions may occur thereby.

[0097] All-solid-state battery

[0098] According to another embodiment of the present disclosure, an all-solid-state battery including the above-mentioned negative electrode is provided. The all-solid-state battery of another embodiment may include: a positive electrode including a positive electrode current collector and a lithium composite oxide-based positive electrode active material layer formed on the positive electrode current collector, and further includes an additional solid electrolyte layer interposed between the positive electrode and the negative electrode.

[0099] The all-solid-state battery of another embodiment including the negative electrode of the above-mentioned one embodiment can exhibit improved life characteristics and safety by fundamentally suppressing the growth of lithium dendrites, while exhibiting high energy density and high capacity characteristics comparable to batteries using existing lithium metal negative electrodes. In addition, the solid electrolyte material is uniformly formed in the nanopores, so that sufficient contact characteristics between the negative electrode and the solid electrolyte, low interface resistance, and excellent ionic conductivity can be ensured.

[0100] In the all-solid-state battery of this other embodiment, an additional solid electrolyte layer may be further included between the positive electrode and the negative electrode. This solid electrolyte layer may include a solid electrolyte and a binder that are the same or different from the solid electrolyte material contained in the nanopores of the negative electrode.

[0101] In addition, such a solid electrolyte layer can be formed by applying a slurry composition containing a solid electrolyte, a binder and a solvent to an electrode of a positive electrode or a negative electrode; or by applying the slurry composition to a separate release paper and drying it to form a solid electrolyte layer, which is then laminated to the electrode; or by impregnating a solid electrolyte into a porous non-woven fabric. However, since the composition and formation method of the additional solid electrolyte layer can follow the composition and formation method of the solid electrolyte layer of an all-solid-state battery conventionally known in the art, additional description thereof will be omitted.

[0102] Due to the addition of this additional solid electrolyte layer, the ionic conductivity and contact characteristics between the electrode and the solid electrolyte can be further improved. In addition, when a porous nonwoven fabric or the like is used, the mechanical properties of the solid electrolyte and the all-solid-state battery can be further improved.

[0103] On the other hand, in the all-solid-state battery of other embodiments, the remaining components (such as the positive electrode) except the negative electrode and the solid electrolyte layer can follow the configuration of a conventional all-solid-state battery. Such a positive electrode may include a positive electrode current collector and a positive electrode active material layer disposed on the positive electrode current collector.

[0104] The positive electrode is manufactured by mixing an active material and a binder, optionally the above-mentioned solid electrolyte (e.g., a sulfide solid electrolyte same as those contained in the negative electrode or the additional solid electrolyte layer), a conductive material, a filler, and the like in a solvent to prepare an electrode mixture slurry, and then applying the electrode mixture slurry to each positive electrode current collector. At this time, the solid electrolyte and the binder are the same as those described above for the negative electrode, etc., and the remaining positive electrode manufacturing method is well known in the art, and thus, a detailed description thereof will be omitted here.

[0105] Meanwhile, in the case of the positive electrode active material, there is no particular limitation as long as it is a lithium composite oxide-based material capable of reversibly inserting and extracting lithium ions. For example, the positive electrode active material may include one or more of a composite oxide composed of lithium and a combination of cobalt, manganese, nickel, iron or a plurality of metals.

[0106] In a more specific example, a compound represented by any one of the following chemical formulae may be used as the positive electrode active material: Li a A 1-b R b D2 (where 0.90≤a≤1.8 and 0≤b≤0.5); Li a E 1-b R b O 2-c D c (where 0.90≤a≤1.8, 0≤b≤0.5, and 0≤c≤0.05); LiE 2-b Rb O 4-c D c (where 0≤b≤0.5,0≤c≤0.05); Li a Ni 1-b-c Co b R c D α (where 0.90≤a≤1.8,0≤b≤0.5,0≤c≤0.05 and 0<α≤2); Li a Ni 1-b-c Co b R c O 2-α Z α (where 0.90≤a≤1.8,0≤b≤0.5,0≤c≤0.05 and 0<α<2); Li a Ni 1-b-c Co b R c O 2-α Z2 (where 0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05 and 0<α<2); Li a Ni 1-b-c Mn b R c D α (where 0.90≤a≤1.8,0≤b≤0.5,0≤c≤0.05 and 0<α≤2); Li a Ni 1-b-c Mn b R c O 2-α Z α (where 0.90≤a≤1.8,0≤b≤0.5,0≤c≤0.05 and 0<α<2); Li a Ni 1-b-c Mn b R c O 2-α Z2 (where 0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05 and 0<α<2); Li a Ni b E c G d O2 (where 0.90≤a≤1.8, 0≤b≤0.9, 0≤c≤0.5 and 0.001≤d≤0.1); Li a Ni b Co c Mn d GeO2 (where 0.90≤a≤1.8, 0≤b≤0.9, 0≤c≤0.5, 0≤d≤0.5 and 0≤e≤0.1); Li a NeG bO2 (where 0.90≤a≤1.8 and 0.001≤b≤0.1); Li a CoG b O2 (where 0.90≤a≤1.8 and 0.001≤b≤0.1); Li a MnG b O2 (where 0.90≤a≤1.8 and 0.001≤b≤0.1); Li a Mn b O4 (where 0.90≤a≤1.8 and 0.001≤b≤0.1); QO2; QS2; LiQS2; V2O5; LiV2O5; LiTO2; LiNiVO4; Li (3-f) J2(PO4)3(0≤f≤2);Li (3-f) Fe2(PO4)3(0≤f≤2); and LiFePO4.

[0107] In the above chemical formula, A is Ni, Co, Mn or a combination thereof; R is Al, Ni, Co, Mn, Cr, Fe, Mg, Sr, V, a rare earth element or a combination thereof; D is O, F, S, P or a combination thereof; E is Co, Mn or a combination thereof; Z is F, S, P or a combination thereof; G is Al, Cr, Mn, Fe, Mg, La, Ce, Sr, V or a combination thereof; Q is Ti, Mo, Mn or a combination thereof; T is Cr, V, Fe, Sc, Y or a combination thereof; and J is V, Cr, Mn, Co, Ni, Cu or a combination thereof.

[0108] Of course, a material having a coating on the surface of the above-mentioned compound can also be used, or a mixture of the above-mentioned compound and a compound having a coating can be used. The coating may include a coating element compound, such as a coating element oxide, a hydroxide, a coating element oxyhydroxide, a coating element carbonate oxide, or a coating element hydroxycarbonate. The compounds forming these coatings may be amorphous or crystalline. As coating elements included in the coating, Mg, Al, Co, K, Na, Ca, Si, Ti, V, Sn, Ge, Ga, B, As, Zr, or a mixture thereof can be used. As a coating formation process, any coating method can be used as long as it can be coated by using these elements in the compound without adversely affecting the physical properties of the positive active material (for example, a spraying method or an impregnation method, etc.). Since this is a content that can be widely understood by those skilled in the art, its detailed description will be omitted.

[0109] The positive electrode collector is generally manufactured to have a thickness of 3 μm to 500 μm. The positive electrode collector is not particularly limited as long as the corresponding battery has high conductivity and does not cause chemical changes in the battery, and for example, the positive electrode collector may be formed of stainless steel, aluminum, nickel, titanium, calcined carbon, or a material formed by surface treating the surface of stainless steel or aluminum with carbon, nickel, titanium, silver or the like. The collector may have fine concave-convex shapes on its surface to enhance the adhesion of the positive electrode active material, and may be formed in various forms such as films, sheets, foils, nets, porous bodies, foams, and non-woven fabric structures.

[0110] The conductive material is not particularly limited as long as the corresponding battery has high conductivity and does not cause chemical changes in the battery, and for example, graphite such as natural graphite and artificial graphite; carbon black such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers such as carbon fibers and metal fibers; metal powders such as carbon fluoride powder, aluminum powder, and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive materials such as polyphenylene derivatives can be used.

[0111] The all-solid-state battery of one embodiment can be used not only in a unit cell used as a power source for a small device, but also as a unit cell in a medium or large-sized battery module including a plurality of battery cells. In addition, a battery pack including the battery module can be configured.

[0112] Hereinafter, preferred embodiments of the present disclosure, comparative examples, and test examples for evaluating them are described. However, the following embodiments are merely preferred embodiments of the present disclosure, and the present disclosure is not limited to the following embodiments.

[0113] Example 1: Fabrication of a negative electrode for an all-solid-state battery

[0114] Carbon paper (HCP010N, Shanghai Hesen Electric Co. Ltd. USA) was purchased and the front and back sides of the carbon paper were subjected to surface oxidation using oxygen plasma treatment. At this time, the plasma treatment was performed by treating the front and back sides with plasma for 15 minutes respectively while flowing a mixed gas of oxygen and argon.

[0115] Next, at room temperature, the surface oxidized carbon paper was placed in 100 ml of methanol dissolved with 2-methyl imidazole (13.136 g, 8 eq), and the mixture was stirred for 6 hours. Then, 100 ml of methanol dissolved with zinc nitrate hexahydrate (5.95 g, 1 eq) was added to the solution, and the mixture was stirred for 12 hours. Thus, carbon paper coated with a zinc organic framework (ZLF-8) was formed.

[0116] After the stirring was completed, the carbon paper coated with the Zn-organic framework was taken out and washed with pure methane for 3-5 times by stirring.

[0117] Then, the carbon paper was kept and dried in an oven at a temperature of about 80° C. under a vacuum state for 12 hours. The process before drying was set once, and the zinc-organic zinc framework coating was repeated twice in total.

[0118] In order to carbonize the dried carbon paper, the carbon paper was heated at 5 °C min -1 The samples were heated to 1000 °C at a heating rate of 1.50 ℃ and then calcined and carbonized in a nitrogen atmosphere for 5 h.

[0119] The carbonized carbon paper was stirred in a 2M hydrochloric acid solution for 6 hours to remove impurity minerals (Zn). The carbon paper was taken out of the hydrochloric acid, immersed in deionized water (DI), washed 3 times, each time for 20 minutes, and finally dried in a vacuum oven at 70°C for 7 hours. According to the above process, an amorphous carbon layer was formed on the crystalline carbon layer of the carbon paper.

[0120] At the same time, Li2S-P2S5 as a sulfide solid electrolyte and NBR as a binder were added to anisole at a weight ratio of 95:5 to prepare a slurry composition (solid content: 60 wt %) for forming a solid electrolyte material. The slurry composition was mixed and formed in a Thinky mixer at a speed of 2000 rpm for 1 minute.

[0121] The slurry composition was bar coated onto the amorphous carbon layer and dried overnight at room temperature / atmospheric pressure to form a solid electrolyte material on the amorphous carbon layer.

[0122] Meanwhile, after forming the battery of Example 2, the electrochemical reaction of the negative electrode of Example 1 was replaced with a charge / discharge process. Through the above process, the negative electrode of Example 1 was manufactured.

[0123] Example 2: Fabrication of an all-solid-state battery including the negative electrode of Example 1

[0124] First, a positive electrode and an additional solid electrolyte layer were prepared by the following method.

[0125] LiNi as the positive electrode active material 0.8 Co 0.1 Mn 0.1 O2, Li2S-P2S5 as a sulfide solid electrolyte, NBR as a binder, and VGCF as a conductive material were added to anisole at a weight ratio of 75.5:22.1:1.5:1 to prepare a slurry composition (solid content: 70 wt %) for forming a positive electrode active material layer. The slurry composition was coated on one surface of an aluminum thin film (thickness: about 10 μm) and dried at 60° C. for 6 hours to prepare a positive electrode.

[0126] In addition, Li2S-P2S5 as a sulfide solid electrolyte and NBR as a binder are added to anisole in a weight ratio of 95:5 to prepare a slurry composition (solid content: 60 weight %) for forming a solid electrolyte layer. The slurry composition is mixed and formed at a speed of 2000rpm in a Thinky mixer for 1 minute. The slurry composition is applied to one surface of a release paper made of polyethylene terephthalate and dried overnight at room temperature and atmospheric pressure, and then the release paper is removed to prepare a solid electrolyte layer. At this time, the thickness of the solid electrolyte layer is 30μm.

[0127] Next, the positive electrode and the solid electrolyte layer were laminated and pressurized at a pressure of 500 MPa for 5 minutes to prepare a laminate of the positive electrode and the solid electrolyte layer. In the obtained laminate, the porosity of the positive electrode was 15% by volume, and the porosity of the solid electrolyte layer was 5% by volume.

[0128] Subsequently, the laminate and the negative electrode prepared in Example 1 were laminated in sequence and pressed at 200 MPa for 5 minutes to obtain an electrode assembly. In each of the above steps, a CIP (Cold isotatic pressing) device was used for pressurization. Through the above process, the all-solid-state battery of Example 2 was manufactured.

[0129] Comparative Example 1 and Comparative Example 2: Fabrication of negative electrode and all-solid-state battery

[0130] A slurry composition having the same composition as that of Example 1 was applied to the carbon paper used as the first raw material in Example 1 by the same method to form a solid electrolyte material.

[0131] An all-solid-state battery including the negative electrode of Comparative Example 1 instead of the negative electrode of Example 1 was manufactured by the same method as in Example 2, and was used as an all-solid-state battery of Comparative Example 2. In Comparative Examples 1 and 2 as described above, after the battery was manufactured, the electrochemical reaction with the negative electrode was replaced by a charge / discharge process.

[0132] Comparative Example 3: Fabrication of negative electrode and all-solid-state battery

[0133] A lithium metal thin film formed to a thickness of 20 μm was used as the negative electrode instead of the negative electrode of Example 1. Specifically, the negative electrode was prepared in a state where the lithium metal thin film having a thickness of 20 μm was attached to the surface of a nickel current collector having a thickness of 10 μm.

[0134] Furthermore, a positive electrode, a solid electrolyte layer, and an all-solid-state battery were sequentially manufactured by the following method: First, a positive electrode was formed in the same manner as in Example 2.

[0135] In addition, Li2S-P2S5 as a sulfide solid electrolyte and NBR as a binder are added to anisole in a weight ratio of 95:5 to prepare a slurry composition (solid content: 60 weight %) for forming a solid electrolyte layer. The slurry composition is mixed and formed at a speed of 2000rpm in a Thinky mixer for 1 minute. The slurry composition is applied to one surface of a release paper made of polyethylene terephthalate and dried overnight at room temperature and atmospheric pressure, and then the release paper is removed to prepare the first solid electrolyte layer. In addition, a separate second solid electrolyte layer is prepared in the same manner as the first solid electrolyte layer. At this time, the thickness of each solid electrolyte layer is 30 μm.

[0136] Next, the positive electrode and the first solid electrolyte layer were laminated and pressurized at a pressure of 500 MPa for 5 minutes to prepare a laminate of the positive electrode and the first solid electrolyte layer. Then, the second solid electrolyte layer was further laminated on the above laminate and pressurized at a pressure of 500 MPa for 5 minutes to prepare a laminate of the positive electrode, the first solid electrolyte layer and the second solid electrolyte layer.

[0137] Subsequently, the laminate and the negative electrode including the lithium metal film were laminated in sequence and pressurized at 200 MPa for 5 minutes to obtain an electrode assembly. In each of the above steps, a CIP (Cold isotatic pressing) device was used for pressurization. Through the above process, the all-solid-state battery of Comparative Example 3 was manufactured.

[0138] Test Example 1: SEM and TEM analysis of the carbon layer of the negative electrode

[0139] In the step before forming the solid electrolyte material in the negative electrode manufacturing process of Comparative Example 1 and Example 1, the surface of each carbon layer was analyzed by SEM and TEM, respectively. The SEM and TEM images are shown as follows, respectively. Figure 1a and Figure 1b shown.

[0140] First, refer to Figure 1a , it was confirmed by SEM images that the carbon layer included in the negative electrode of Comparative Example 1 was an electrode in which carbon fibers with a diameter of 3 μm to 5 μm were aggregated. Figure 1b , it was confirmed that the negative electrode of Example 1 was formed of a network defect carbon layer on the fiber surface of the crystalline carbon layer.

[0141] In addition, refer to Figure 1a In the TEM image in the comparative example 1, the 100-plane (the lattice spacing of the 100-plane is 0.341 nm) as a regular carbon crystal plane is observed in the carbon layer. Through FFT analysis, it can be seen that the electrode is composed of a crystalline carbon layer in which there is a very regular carbon arrangement. Figure 1b From the TEM images in FIG. 1 , it can be seen that a plurality of defective layers with a thickness of about 1.03 nm are generated on the surface of the carbon layer of Example 1, and unlike Comparative Example 1, FFT analysis shows that disordered and amorphous carbon is generated.

[0142] Test Example 2: EDS Analysis of the Carbon Layer of the Negative Electrode

[0143] In the step before forming the solid electrolyte material, for each manufacturing step of Example 1, EDS was used to perform elemental analysis on the carbon paper and the negative electrode. The analysis results are as follows: Figure 2a to Figure 2c and its corresponding SEM image. The element contents of each manufacturing step based on the analysis results are summarized in Table 1 below. During the EDS elemental analysis, in order to confirm whether the zinc-organic framework (ZLF-8) is formed and removed by carbonization during the manufacturing process, the contents of four elements, carbon, oxygen, nitrogen and zinc, were analyzed.

[0144] Specifically, the element analysis results of (a) the carbon paper in the first raw material state ( Figure 2a ), (b) Elemental analysis results before carbonization ( Figure 2b ), and (c) elemental analysis results after the amorphous carbon layer was formed by carbonization ( Figure 2c ) were distinguished and summarized.

[0145] [Table 1]

[0146]

[0147] Refer to Table 1 and Figure 2a to Figure 2cThe elemental analysis results in the results confirm that the zinc organic framework is formed and coated on the carbon paper by the reaction of the zinc precursor and the nitrogen precursor (methylimidazole) before the carbonization step, and then completely removed by carbonization and calcination, so it does not remain in the final negative electrode and amorphous carbon layer.

[0148] Therefore, it can be confirmed that the characteristics of the negative electrode finally formed in Example 1 depend only on the formation of the carbon defect structure and not on the zinc-organic framework.

[0149] Experimental Example 3: Carbon defect structure and nanopore analysis of amorphous carbon layer (XPS, Raman spectroscopy and BET surface analysis)

[0150] First, in the step before forming the solid electrolyte material in the negative electrode manufacturing process of Comparative Example 1 and Example 1, each carbon layer was analyzed by XPS. The analysis results are as follows: Figure 3 See Figure 3 It can be confirmed that in Example 1, a large number of nanopores (vacancy) are formed in the carbon layer due to the process of forming and coating the zinc organic framework and then carbonizing and removing it.

[0151] In addition, according to the XPS analysis results of Comparative Example 1 and Example 1, a carbon defect structure including electron-deficient carbon atoms, specifically a single peak (non-conjugated C peak) originating from a nanopore, was confirmed. Specifically, the analysis results of Example 1 showed that the intensity ratio of the single peak originating from such a carbon defect structure / the peak originating from carbon having an sp2 orbital hybrid structure (normal carbon without an electron-deficient state) was 0.403, which was stronger than that of Comparative Example 1, whose intensity ratio was 0.175.

[0152] This confirmed that a carbon defect structure including nanopores and electron-deficient carbon atoms was formed at a high density on the amorphous carbon layer included in the negative electrode of Example 1.

[0153] At the same time, Raman spectroscopy analysis was performed on the carbon layers formed in Comparative Example 1 and Example 1, and the analysis results are as follows: Figure 4 shown.

[0154] Reference Figure 4 It can be confirmed that in the electrode of Example 1, the 1100-1500 cm -1 The peak (D band; peak of electron-deficient carbon originating from carbon defect structure) shows a peak greater than or equal to 1500 cm -1 and 2000cm -1 The intensity of the peak observed below (G band; peak derived from normal carbon having a graphitic structure) and their intensity ratio are defined as I D / I GIn contrast, in the electrode of Comparative Example 1, it can be confirmed that the D / I G The intensity ratio of the defined peak is as low as 0.788.

[0155] According to the results of Raman spectroscopy analysis, it can be confirmed that, in the negative electrode of Example 1, electron-deficient carbon atoms and carbon defect structures including the electron-deficient carbon atoms are formed on the amorphous carbon layer at a considerable ratio and high density.

[0156] In addition, according to the results of Raman spectroscopy analysis of Example 1, it was confirmed that -1 There is a 2D peak with a graphene layer number having a considerable intensity near the G peak. Such a peak was not confirmed in Comparative Example 1. From the fact that the 2D peak appears with an intensity ratio of about 0.34 compared to the G peak, it is confirmed that the amorphous carbon layer included in the negative electrode of Example 1 is formed into a shape including a plurality of graphene layers. For reference, it is known that a value of about 4 in the 2D / G ratio generally indicates a single layer graphene, and a value of less than 1 indicates a multilayer graphene.

[0157] Finally, the carbon layer surfaces of Example 1 and Comparative Example 1 were subjected to BET analysis. The results are as follows: Figure 5 More specifically, BET pore analysis was performed using nitrogen adsorption. Figure 5 It can be confirmed that pores between 20 and 120 nm are formed in the carbon layer of Comparative Example 1, while nanopores with a size of about 1.1 nm are mainly formed in the electrode of Example 1. It can be confirmed that the nanopores of Example 1 correspond to the high-density carbon defect structure confirmed by the XPS and Raman spectroscopy analysis results.

[0158] Test Example 4: Evaluation of negative electrode surface characteristics after solid electrolyte material formation

[0159] In Example 1 and Comparative Example 1, the surface of the negative electrode after forming the solid electrolyte material was analyzed by SEM and shown in Figures 6a to 6d More specifically, Figure 6a is a SEM photograph of the front surface of the negative electrode after the solid electrolyte material is formed in Example 1, Figure 6b and Figure 6c This is a SEM photo of the rear surface of this negative electrode. Figure 6d is a SEM photograph of the rear surface of the negative electrode after the solid electrolyte material was formed in Comparative Example 1.

[0160] Reference Figures 6a to 6dIt can be confirmed that in the negative electrode of Example 1, the solid electrolyte material fully penetrates from the front surface of the negative electrode to the rear surface and is uniformly formed in the nanopores of the amorphous carbon layer. In contrast, in the negative electrode of Comparative Example 1, the solid electrolyte material is not fully penetrated / formed to the rear surface of the negative electrode.

[0161] In summary, it can be confirmed that in the negative electrode of Example 1, due to the nanoporous structure of the amorphous carbon layer, sufficient contact characteristics between the negative electrode and the solid electrolyte can be ensured.

[0162] Test Example 5: Lifespan Characteristics Evaluation of All-Solid-State Batteries

[0163] The life characteristics of the batteries of Example 2, Comparative Example 2 and Comparative Example 3 were evaluated and compared. The results are shown in FIG. Figure 7 More specifically, these life characteristics were evaluated by the following methods.

[0164] First, an all-solid-state battery with a capacity of 20.8 mAh was manufactured by the methods of the embodiments and comparative examples, and was charged at 4.25 V (0.05 C cut-off) 0.1 C in CC-CV mode, and discharged to 3 V at 0.1 C to perform a charge / discharge test and an electrochemical reaction. The charge / discharge test cycle was repeated, and the capacity retention rate of the discharge capacity was determined.

[0165] Reference Figure 7 It can be confirmed that the battery of Example 2 shows significantly improved capacity retention and life characteristics compared with the batteries of Comparative Examples 2 and 3. It is expected that this is because the growth of lithium dendrites is effectively suppressed in the negative electrode and the battery of Example 2, and the negative electrode and the solid electrolyte show excellent contact characteristics and ion conductivity.

[0166] In contrast, the battery of Comparative Example 2 not only has poorer capacity retention and life characteristics than Example 2, but also suffers from a short circuit during the evaluation of life characteristics, and the evaluation of life characteristics is stopped at a time point of about 35 cycles. In addition, it can be confirmed that the battery of Comparative Example 3 shows significantly poorer life characteristics than the examples due to the growth of lithium dendrites in the negative electrode, etc.

Claims

1. An all-solid-state battery, comprising: a positive electrode, the positive electrode comprising a positive electrode current collector and a lithium composite oxide-based positive electrode active material layer formed on the positive electrode current collector; Anode for all-solid-state batteries, including: Crystalline carbon layer; an amorphous carbon layer including a carbon defect structure formed on the crystalline carbon layer and formed of electron-deficient carbon atoms, and wherein nanoscale pores are formed in the carbon defect structure; and a solid electrolyte material, a portion of which is formed in the pores of the amorphous carbon layer and another portion of which is interposed between the positive electrode and the negative electrode; wherein Raman spectrum analysis of the amorphous carbon layer shows a peak of a D band originating from a carbon defect structure and a peak of a G band originating from normal carbon having a graphite structure, and is defined as an intensity ratio of a peak of the D band / a peak of the G band of 1.1 to 1.5, and Wherein, the diameter of the pore is 0.5nm to 2nm. 2 . The all-solid-state battery according to claim 1 , wherein the solid electrolyte material comprises a sulfide solid electrolyte and a binder.

3. The all-solid-state battery according to claim 2, wherein the sulfide solid electrolyte comprises a sulfide-based compound of the following Chemical Formula 1: [Chemical formula 1] M 1 a M 2 b S c X 1 d In the chemical formula 1, M 1 is at least one selected from alkali metals and alkaline earth metals, and M 2 is Sb, Sn, Mg, Ba, B, Al, Ga, In, Si, Ge, Pb, N, P, As, Bi, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Y, Zr, Nb, Mo, Tc, Ru, Rh, Pd, Ag, Hf, Ta, W or La, X 1 is F, Cl, Br, I, Se, Te or O, 0 < a ≤ 6, 0 < b ≤ 6, 0 < c ≤ 6, and 0 ≤ d ≤ 6. 4 . The all-solid-state battery according to claim 2 , wherein the adhesive comprises an acrylic adhesive, a polyvinylidene fluoride (PVDF)-based adhesive, a polytetrafluoroethylene (PTFE)-based adhesive, or a butadiene rubber-based adhesive. 5 . The all-solid-state battery according to claim 1 , wherein the crystalline carbon layer comprises a plurality of carbon fibers and has a thickness of 1 μm to 50 μm. The all-solid-state battery according to claim 1 , wherein the amorphous carbon layer has a thickness of 1 nm to 100 nm.

7. The all-solid-state battery according to claim 1, wherein the negative electrode further comprises lithium ions or lithium carbide compounds embedded in the amorphous carbon layer, and lithium metal electrodeposited around the lithium ions or lithium carbide compounds. 8 . The all-solid-state battery according to claim 7 , wherein the lithium ions or the lithium carbide compound are two-dimensionally combined with the lithium metal on the same plane as the amorphous carbon layer.

9. The all-solid-state battery according to claim 8, wherein lithium derived from the lithium ions or lithium carbide compounds donates electrons to electron-deficient carbon atoms and bonds to the carbon defect structure. 10 . The all-solid-state battery according to claim 1 , wherein the solid electrolyte material is formed by applying a slurry composition including a sulfide solid electrolyte, a binder, and a solvent onto the amorphous carbon layer.

11. The all-solid-state battery according to claim 1, wherein the negative electrode for the all-solid-state battery is manufactured by a method comprising the following steps: treating a crystalline carbon fabric including a plurality of carbon fibers with oxygen plasma to oxidize the surface; reacting the surface-oxidized crystalline carbon fabric, a nitrogen precursor, and a metal precursor to form a carbon fabric coated with a metal organic framework; calcining and carbonizing the carbon fabric coated with the metal organic framework at a temperature of 700° C. or higher to form the amorphous carbon layer on the crystalline carbon fabric; as well as A slurry composition including a solid electrolyte, a binder, and a solvent is coated on the amorphous carbon layer and dried.

12. The all-solid-state battery according to claim 11, wherein the metal organic framework is a metal zeolite-imidazole structure formed by a nitrogen precursor and a metal precursor, wherein the metal precursor is a compound comprising at least one metal-containing compound selected from the group consisting of zinc (Zn), aluminum (Al), copper (Cu), zirconium (Zr), iron (Fe), chromium (Cr), and gadolinium (Gd), and nitrates, hydroxides or sulfates of these metals, or hydrates and / or solvates thereof; The nitrogen precursor is an imidazole compound.